Nitrite and Nitrate Concentrations in the Drinking Groundwater of Shiraz City, South-central Iran by Statistical Models - Ahmad BADEE NEZHAD; Mohammad Mahdi EMAMJOMEH; Mahdi FARZADKIA; Ahmad JONIDI JAFARI; Mehrab SAYADI; Amir Hossein DAVOUDIAN TALAB (Tehran University of Medical Sciences, 2017)
Background: Nitrite (NO2-) and nitrate (NO3-) contaminations of groundwater are considered as one of the major health challenges in recent decades. This study aimed to evaluate the nitrite and nitrate concentrations in the drinking groundwater of Shiraz, South-central Iran by statistical models. Methods: From 43 active wells of Shiraz drinking water supplies, 344 samples were collected in the high and low precipitation seasons from 2010 to 2014. Nitrate and nitrite concentrations were tested by a DR6000 spectrophotometer, and the results were analyzed by different software, including SPSS ver. 20, ArcView GIS 9.3. It was done by variable and multivariate regression models. In all tests, the level of significance was set at 5%. Results: Nitrate concentrations in the samples were in the range of 5 to 72 mg/l, and 38 (11%) of the samples had nitrate concentrations above the standard level 10 mg/L as nitrogen. The annual mean concentration of nitrite varied from 0 to 0.025 mg/l. There was an inverse correlation between nitrate and nitrite concentrations and well depths. Conclusion: The most important reason for the high concentration of nitrate in Shiraz drinking groundwater supplies were lack of health privacy of wells, the impact of residential construction around drinking water wells, and placement of wells in the direction of groundwater flow.